California Delegation Newsletter 1976 (1976)
The California Delegation Newsletter outlines key meetings and events for delegates attending the 1976 Democratic National Convention in New York, including a delegation caucus and welcoming reception on July 11 at the New York Hilton. It lists delegation officers, press and administrative office locations, convention session start times, and numerous Sunday caucuses, fundraisers, and social events hosted by various groups and campaigns. The newsletter also provides transportation details, noting that charter buses will run between the Hilton and Madison Square Garden before and after convention sessions.